140 Evolving Technical Approach and Results in Hypoplastic Left Heart Syndrome with Intact or Highly Restrictive Atrial Septum. (6th June 2015) - Duong, Phuoc; McBrien, Angela; Crossland, David; O'Sullivan, John; Hasan, Asif; Griselli, Massimo
Abstract : Background: We describe our current unit approach and report interstage results in the HLHS with Intact atrial septum (IAS) or highly restrictive interatrial communication (HRIC). Method: A retrospective review of the institutional HLHS programme (2005–2014). Advances in fetal diagnosis lead to delivery planning in hybrid theatre: median sternotomy and interventional defect creation/enlargement. Results: 9 neonates (4 IAS and 5 HRIC) and 5 required immediate intervention postnatally. Delayed/insufficient septostomy in 3 HRIC resulted in death before stage I Norwood even with ECMO support in 2/3. Of the other 6, 2 had trans-atrial stent placement and 1 trans-atrial balloon septostomy (3 had surgical septectomy). 5/6 underwent concomitant bilateral pulmonary artery banding. All the 6 patients reached the Norwood procedure after 27 ± 21 days and 50% required ECMO postoperatively. Trans-atrial stenting resulted in less pre Norwood morbidities. There was no stent-related complications. There was no hospital mortality after Norwood and current inter-stage survival is 100%: 5 patients underwent successfully second-stage palliation, 1 of them had the Fontan completion and subsequently transplanted. Conclusion: Together with advanced fetal diagnosis, effective left atrial decompression especially with trans-atrial stunting using hybrid technique and availability of mechanical support can improve the outcome of HLHS/IAS/HRIC with low interstage morbidity and excellent survival.